Agronomic behavior of bell pepper cultivars (Capsicum annuum L.) cultivated in open f ield and under protected conditions - Lozano-Fernández, Jaime; Orozco-Orozco, Luz Fanny; Grisales-Vásquez, Nancy Yohana (REVISTA TERRA LATINOAMERICANA, 2022)
The bell peppers (Capsicum annuum L.) cultivars grown in Colombia come from countries with temperate zones, which limits their production in climate and agroecological conditions of the country, since they do not reach their adaptability and potential yield, due to factors that af fect gene expression. In Colombia, 95% of bell peppers are sowed in open f ield. However, farmers seek to improve their yields by growing them under protected condition with plastic cover and natural ventilation. Therefore the objective of this study is to evaluate fruit yield and pest and disease incidence of four bell pepper cultivars (BG2, Cuadrado rojo, Cacique and Nathalie) grown under three types of environments: open f ield in 2014 and protected in two cycles (2013 and 2014). The trials were conducted under multilocation trials with a randomized complete block design (RCBD) at La Selva Research Center (AGROSAVIA), located in Rionegro-Antioquia (Colombia). The following variables were measured: fruit yield, number, length and diameter per category. Incidence of pests and diseases were also recorded. No signif icant statistical dif ferences were found among yields obtained under the dif ferent environments. The genetic ef fect of cultivars was more determinant than the ef fect of environments on yield variables. In protected environments, Cacique and Nathalie cultivars had the highest yield, while BG2 and Cuadrado rojo had the highest rejected fruit yield. The incidence of the main pests and diseases was irregular, which was higher under protected conditions and had no direct connection with the cultivars.